Relevansi Ajaran Suku Samin “Uri-uri Pambudi” dan Karakter Pancasila Sekolah Dasar - Nugraheni, Setyo Wuri Kartika; Dinia, Annisa Fatkhiya; Ardianzah, Ramadhan Dwi; Kusumadewi, Rida Fironika (Program Studi Tadris IPS Fakultas tarbiyah IAIN Kudus, 2025)
This paper explores the practical integration of Samin teachings in Pancasila character public education system Elementary School 1 Klopoduwur. The issues raised were the obstacles in embedding cultural heritage into academic programs and students' understanding of Pancasila values that are relevant to everyday life. The method used was a case studies qualitative approach with data collection techniques through observation and interviews with principals, teachers, and students. The results showed that students had applied Pancasila values, such as critical reasoning, creativity, independence, faith, noble character, mutual cooperation, and global diversity, which are in line with the teachings of“Uri-uri Pambudi” from the Samin Tribe. However, there are still challenges in student understanding and integration of Samin teachings into the curriculum. This study recommends increased training for teachers and the development of activities that involve students more to optimize the implementation of character education.